Eating patterns of Turkish adolescents: a cross-sectional survey - AKMAN, MEHMET (BMC, 2010)
Background: Adolescence is a crucial period for development of dietary behaviors that continue into adulthood and influence the risk of chronic diseases later in life. The aim of this study was to determine the eating patterns of adolescents' and their compliance with the Food Guide Pyramid. Methods: 625 students, aged between 11-15 years, from an elementary school in Istanbul, Turkey were enrolled in this cross-sectional survey. A questionnaire of eating patterns (QEP) was administered to all participants. QEP is consisted of questions assessing the knowledge and behaviors on healthy eating, factors affecting food choice, physical activity status and demographical variables. Height and weight of all participants were measured. Physical activity status was determined by questioning about participation in regular sport activities, how much time spent watching TV, playing computer games or doing homework. Results: The mean age of the participants was 12.15 +/- 1.15 and 50.5% were female. According to body mass index (BMI) percentiles, 8.3% (52) were obese and 10.2% were overweight. 51% had breakfast every day and only 1.9% met all the recommendations of the Food Guide Pyramid. Among the participants, 31% have fast food at least once every day and 60.8% skip meals. When participants were asked to rate the factors effecting their food choice according to a 10 point Likert scale, the highest mean scores (high impact on food choice) were for the factors; family, health, body perception, teachers and friends; 7.5 +/- 3.1, 7.4 +/- 3.1, 6.1 +/- 3.2, 4.8 +/- 3.3 and 4.2 +/- 3.0 respectively. Total mean time spent on all passive activities (TV, computer, reading homework etc) per day was 9.8 +/- 4.7 hours. Conclusions: In this study we have demonstrated that, adolescents do not have healthy eating patterns. Educational interventions should be planned to decrease the health risks attributable to their eating behaviors.
Keywords: BODY-MASS INDEX; PHYSICAL-ACTIVITY; FAST-FOOD; CHILDREN; RECOMMENDATIONS; ASSOCIATIONS; OBESITY; SCHOOL; HOME; CONSUMPTION